Risk to public safety posed by adjudicated delinquent juvenile sex offenders: Do they really need to register - Mynatt, Donna Susan (2013)
This study examined sexual and non-sexual recidivism among a sample of delinquent juvenile sexual offenders (JSOs) following commitment to a state juvenile correctional agency. Both juvenile and adult recidivism rates were studied. The results showed a low rate of sexual recidivism and a high rate of non-sexual recidivism across a 4-year follow-up period past age18. Logistic and linear regression identified 4 significant predictor variables of non-sexual recidivism. JSOs that were non-white, un-related to the victim in the initial offense, or used another location for the initial offense other than their own home, were significantly more likely to commit non-sexual recidivism. Additionally, JSOs who received sex-offender treatment only in the community displayed more serious non-sexual recidivism. The discussion includes the limitations of the study as well as theoretical and policy implications. The results support the use of re-integrative interventions as opposed to disintegrative stigmatizing ones such as sex-offender registration and notification policies